THE INVESTIGATION ON APPLICATION OF GENRE BASED APPROACH (GBA) TO IMPROVE STUDENTS' WRITING ABILITY ON PROCEDURAL TEXT IN EFL CLASSROOM - Jupri, Jupri; Muzakkir, Muzakkir (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2021)
This study investigated the application of Genre-Based Approach (GBA) to improve students` writing ability on procedural text in EFL classroom and to investigate the students` perception of using Genre-Based Approach in improving their writing ability in MA Safinatunnaja NW Repok Oak. The researchers utilized Classroom Action Research (CAR) that was applied in two cycles. Cycle 1 was done in three meetings and cycle 2 was in two meetings. Each cycle consisted of some phases such as planning, action, observation, and reflection. The instruments used by the researchers were observation sheet, questionnaire and writing test. This research took 24 students as the sample. The data obtained were analyzed by using descriptive statistic and inferential statistic through SPSS software version 24. The research resulted that Genre Based Approach gave greater contribution to the students’ writing procedural text. There was an improvement of students` perception in learning process. It was proven by the result of inferential statistical analysis either in cycle 1 or cycle 2. There was a significant improvement between the result of cycle 1 and cycle 2, where in cycle 2 showed significantly greater improvement (M = 82,08) than the cycle 1 (M = 73,33). The sig. 2 tailed between both cycle 1 and cycle 2 was 0,000. This led to the conclusion that the application of Genre Based Approach improved the students’ writing skill. Genre Based Approach was positively improving students` writing ability.